A Review of Recent Research on Individual‐Level Score Reports. Issue 3 (2nd April 2018) - Gotch, Chad M.; Roduta Roberts, Mary
Abstract: As the primary interface between test developers and multiple educational stakeholders, score reports are a critical component to the success (or failure) of any assessment program. The purpose of this review is to document recent research on individual‐level score reporting to advance the research and practice of score reporting. We conducted a search for research studies published or presented between 2005 and 2015, examining 60 scholarly works for (1) the research focus, (2) stated or implied theoretical frameworks of communication, and (3) the characteristics of data sets employed in the studies. Results show that research on score properties, especially subscores, and score report design/layout are well‐represented in the literature base. The predominant approach to score reporting has been through a cybernetics tradition of communication. Data sets were often small or localized to a single context. We present example research questions from novel communication frameworks, and encourage our colleagues to adopt new roles in their relationships to stakeholders to advance score reporting research and practice.